Geriatrics, Covid-19 Pandemic and Challenges - Venkanna Rao, Bhagya (Journal of Pharmacy Practice and Community Medicine)
Rise in life expectancy and decrease in mortality has resulted in an extremely faster rate of geriatrics in India. The majority of the elderly population in India is underprivileged with low education and lesser cleanliness. These geriatrics because of age, suffer from several diseases like diabetes, hypertension, stroke, cardiovascular and respiratory disease, dementia, and other neurodegenerative conditions. Apart from these, they do have compromised immunity which makes them vulnerable to a number of infections. The aged people are the most susceptible individuals to Covid-19 infections throughout the world and also in India. The National Bureau of Economic Research, USA indicated that the severity of infection and casualty is highest in the geriatric population. Research showed that 53% of people more than 60 years of age died in India due to the Covid-19 pandemic compared to younger individuals where death was only 10%.